2016
DOI: 10.1155/2016/6860573
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Acute Physical Exercise on Memory, Peripheral BDNF, and Cortisol in Young Adults

Abstract: In animals, physical activity has been shown to induce functional and structural changes especially in the hippocampus and to improve memory, probably by upregulating the release of neurotrophic factors. In humans, results on the effect of acute exercise on memory are inconsistent so far. Therefore, the aim of the present study was to assess the effects of a single bout of physical exercise on memory consolidation and the underlying neuroendocrinological mechanisms in young adults. Participants encoded a list … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
108
1
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(141 citation statements)
references
References 73 publications
11
108
1
10
Order By: Relevance
“…24 Several studies have shown that, compared to low-intensity activity or a resting state, a high level of aerobic exercise induces an increase in BNDF concentration, which positively affects cognitive function. 25,26 It is also consistent with Davey's exercise-arousal cognition-interaction theory, 12 which predicts a linear relation between effort intensity, arousal level, and cognitive performance.…”
Section: Effect Of Acute Intensification Of Physical Effort (Shorttersupporting
confidence: 79%
See 1 more Smart Citation
“…24 Several studies have shown that, compared to low-intensity activity or a resting state, a high level of aerobic exercise induces an increase in BNDF concentration, which positively affects cognitive function. 25,26 It is also consistent with Davey's exercise-arousal cognition-interaction theory, 12 which predicts a linear relation between effort intensity, arousal level, and cognitive performance.…”
Section: Effect Of Acute Intensification Of Physical Effort (Shorttersupporting
confidence: 79%
“…24 Several studies have shown that, compared to low-intensity activity or a resting state, a high level of aerobic exercise induces an increase in BNDF concentration, which positively affects cognitive function. 25,26 It is also consistent with Davey's exercise-arousal cognition-interaction theory, 12 which predicts a linear relation between effort intensity, arousal level, and cognitive performance.In addition, our study revealed some subtle effects that may contribute to the modification of the motor resonance condition. Undoubtedly, the highest levels of physical exercise (E120%) induced an enhancement in the participants' ability to recognize all types of facial expressions.…”
supporting
confidence: 79%
“…While studies of cognitive and motor learning have assessed the relationship between high intensity exercise, peripheral serum BDNF, and cognitive and motor learning (Skriver, Roig et al 2014, Etnier, Wideman et al 2016, Hotting, Schickert et al 2016), to our knowledge, this is the first study to also include the BDNF Val66Met polymorphism. There are several novel findings of this study that can advance our understanding of the role of exercise and BDNF in motor learning.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that the cortisol released improves learning and memory by interacting with glucocorticoid and mineralocorticoid receptors located in the hippocampus, amygdala, and PFC regions of the brain (Heffelfinger and Newcomer, 2001;Yuen et al, 2009). A positive correlation was detected between the increase in cortisol release after exercise and vocabulary retention among healthy adults (Hötting et al, 2016). Interestingly, cortisol released in response to a psychosocial stress task resulted in an impaired retrieval of words (Tollenaar et al, 2008).…”
Section: Neuroendocrine and Myokinesmentioning
confidence: 96%